Thermoanalytical study and characterization of native starches of Paraná pine seeds (Araucaria angustiofolia, Bert O. Ktze) and European chestnut seeds (Castanea sativa, Mill) - Bicudo, S. C.W.; Demiate, I. M.; Bannach, G.; Lacerda, L. G.; Filho, M. A. S. Carvalho; Ionashiro, M. [UNESP]; Schnitzler, E. (Ecletica Quimica, 2009)
Starch is the most important carbohydrate storage in plants. It is a raw material with diverse botanical origins, and is used by the food, paper, chemical, pharmaceutical, textile and other industries. In this work, native starches of Paraná pine seeds (pinhão) (Araucaria angustiofolia, Bert O. Ktze) and european chestnut seeds (Castanea sativa, Mill) were studied by thermoanalytical techniques: thermogravimetry (TG), differential thermal analysis (DTA) and differential scanning calorimetry (DSC), as well as X-ray powder patterns diffractometry. Apparent and total amylose content was also determined.
Keywords: Enthalpy; Gelatinization; Starch; Thermal analysis